Inhibition of ATP synthesis by fenbufen and its conjugated metabolites in rat liver mitochondria. (March 2016) - Syed, Muzeeb; Skonberg, Christian; Hansen, Steen Honoré
Abstract: Fenbufen is an arylpropionic acid derivative belonging to the group of non-steroidal anti-inflammatory drugs (NSAIDs). Even though fenbufen is considered a safe drug, some adverse reactions including hepatic events have been reported. To investigate whether mitochondrial damage could be involved in the drug induced liver injury (DILI) by fenbufen, the inhibitory effect of fenbufen and its conjugated metabolites on oxidative phosphorylation (ATP synthesis) in rat liver mitochondria was investigated. Fenbufen glucuronide (F-GlcA), fenbufen- N -acetyl cysteine-thioester (F-NAC) and fenbufen- S -glutathione thioester (F-SG) were found to be more potent inhibitors compared to parent fenbufen (F), whereas fenbufen- O- carnitine (F-carn), fenbufen-glycine (F-gly) and fenbufen- N -acetyl lysine amide (F-NAL) were less potent compared to fenbufen. Fenbufen-CoA thioester (F-CoA) was equally potent as fenbufen in inhibiting ATP synthesis. Fenbufen showed time and concentration dependent inhibition of ATP synthesis with Kinact of 4.4 min − 1 and KI of 0.88 μM and Kinact /KI ratio of 5.01 min − 1 μM − 1 . Data show that fenbufen did not act through opening MPT pore, nor did incubation of mitochondria with reduced GSH and fenbufen show any protective effect on fenbufen mediated inhibition of oxidative phosphorylation. Inclusion of NADPH in mitochondrial preparations with fenbufen did not modulate the inhibitory effects, suggesting no role of CYP mediated oxidative metabolites on the ATP synthesis in isolated mitochondria. The results from the present experiments provide evidence that fenbufen and its metabolites could be involved in mitochondrial toxicity through inhibition of ATP synthesis. Highlights: Fenbufen/its conjugated metabolites inhibited oxidative phosphorylation (oxphos). F-GlcA, F-NAC and F-SG are potent inhibitors compared to fenbufen (F). Fenbufen has shown time dependent (mechanism based) inhibition of oxphos. NADPH/GSH/cyclosporine/EGTA did not modulate the inhibitory effects of fenbufen. Inhibitory effects of (F) on oxphos are not mediated through opening of MPT pore.